Aulas Paraná e o registro de classe online (RCO) no ensino de geografia em Marechal Cândido Rondon, Pr: elementos para a análise - Schreiner, Simony (2024)
Geography teachers face daily challenges in building learning, which can lead to a lack of interest in teaching the subject and schooling. These difficulties have become even more evident with the arrival of SARS-CoV-2. Hence, the remote learning system was adopted in the state of Paraná, using Google Classroom as the official teaching and learning platform of the Paraná State Department of Education (SEED, acronym in Portuguese). This scenario has directly impacted on the work organization and performance of teachers, as seen in the slides provided by the Online Class Register. To understand how teachers interact with these materials, data were collected from the APP Sindicato website, and conversations were held with teachers regarding their use of the Online Class Register slides. This qualitative research involved Geography teachers from the state school system in the municipality of Marechal Cândido Rondon, who contributed through interviews and semi-structured questionnaires. The dissertation results indicate that educational practices in Paraná, mediated by digital platforms, are based on a neotechnicist approach, with strong supervision and instrumental standardization. Furthermore, the findings highlight how technology functions as an ideological mechanism and how education is influenced by international corporations within the educational landscape.